2019
DOI: 10.1016/j.hpb.2019.10.1322
|View full text |Cite
|
Sign up to set email alerts
|

Early enteral versus total parenteral nutrition in patients undergoing pancreaticoduodenectomy: a randomized multicenter controlled trial (Nutri-DPC)

Abstract: Background: A recent survey revealed that many European surgeons have concerns about the oncological safety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 0 publications
1
50
0
2
Order By: Relevance
“…S4, supporting information). Rather, POPF occurred more frequently in patients with nasojejunal tube feeding than among those who received parenteral nutrition (OR 2⋅67, 1⋅43 to 5⋅01; P = 0⋅002; I 2 = 0 per cent) 20,21 .…”
Section: Enteral Versus Parenteral Nutritionmentioning
confidence: 97%
See 3 more Smart Citations
“…S4, supporting information). Rather, POPF occurred more frequently in patients with nasojejunal tube feeding than among those who received parenteral nutrition (OR 2⋅67, 1⋅43 to 5⋅01; P = 0⋅002; I 2 = 0 per cent) 20,21 .…”
Section: Enteral Versus Parenteral Nutritionmentioning
confidence: 97%
“…All studies were graded as high risk for performance bias (blinding of participants) because the nutrition route was apparent to the clinical staff. In five studies 20,23,[25][26][27] attrition bias (incomplete outcome data) was reduced by the performance of intention-to-treat analyses. Table 3 summarizes the statistical findings of meta-analyses comparing enteral nutrition with non-enteral nutrition, enteral nutrition with parenteral nutrition, enteral feeding using a percutaneous tube with parenteral nutrition, and enteral feeding using a nasojejunal tube with parenteral nutrition.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the outcomes of enteral nutrition and parenteral nutrition are major concerns among clinicians. Previous studies have demonstrated conflicting results among patients who received enteral nutrition versus those who received parenteral nutrition [1113].…”
Section: Introductionmentioning
confidence: 99%